Peran Orangtua Dalam Mendampingi Kegiatan Belajar Anak Usia Dini - Oktaviana, Anita; Purwanti, Elly (Jurnal Golden Age, 2025)
Early childhood basically spends more time playing than studying. This will certainly have an impact on children's learning activities. The purpose of this study is to describe the role of parents in assisting early childhood learning activities. This type of research is field research using a descriptive qualitative approach. The data in this study were obtained through observation, interviews and documentation. In analyzing the data, researchers used three stages, namely reduction, data presentation, and drawing conclusions. Based on the results of this study, it can be concluded that parents have a very important role in accompanying early childhood learning activities including: giving children habituation as in everyday life, namely getting children to respect other people. Furthermore, the supporting and inhibiting factors of parents when accompanying children include: applying the lessons that have been given by the teacher at school and parents being impatient when accompanying children in learning activities at home.